The Impact of Successful Percutaneous Coronary Intervention on the Reduction of Major Cardiovascular Events in Patients with Chronic Total Coronary Occlusion In dr. Saiful Anwar's Malang Hospital - Ratna Pancasari; Mohammad Saifur Rohman; Ardian Rizal; Novi Kurnianingsih; Anna Fuji Rahimah (Universitas Brawijaya, 2022)
Background: Chronic total coronary occlusion (CTOs) is associated with an increased risk of adverse clinical outcomes. The benefits of percutaneous coronary intervention (PCI) in CTO are still being debated due to the limited data available. This study aims to determine the relationship between the success of PCI in CTOs and the reduction of major cardiovascular events compared to those who failed or did not perform revascularization in patients with chronic coronary total occlusion in RSUD by Dr. Saiful Anwar Malang. Methods:This study is an analytic observational study with a retrospective cohort design. Of a total of 2165 patients who underwent angiography at Saiful Anwar Hospital, Malang, for the period August 2017–September 2020, consecutively, 578 patients with lesions of at least one CTO were found. There were 68 patients who were excluded, so 510 patients were analyzed in this study. They were divided into two groups, the CTO group that was successfully revascularized with PCI (n = 141) and the group that was not revascularized (n = 369). The outcome of this study was major cardiovascular events (MACE), which included cardiac mortality , all cause mortality, and rehospitalization events. Result: Patients with CTO who were not revascularized compared to those with revascularized CTO had a higher history of heart failure, involvement of LM disease, multivessel disease, and three vessel disease (41.2% vs 18.4%, p = 0.041; 16.5% vs 1.8%, p < 0.001; 69.4% vs 22.7%, p < 0.001; 56.5% vs 14.1%, p < 0.001) with a lower mean LVEF (0.49 ± 0.06 vs 0.51 ± 0.07, p=0.045) and older age (60±9 vs 57±8 years ; p=0.007).. At a 12-month follow-up, in the CTO group that was successfully revascularized by PCI, there was a better prognosis than the non-revascularized CTO group in terms of major cardiovascular events (19.9% vs 33.1% Plog-rank = 0.002). These results were consistent for all-cause mortality (5.5% vs 20.6%, Plog-rank =0.027), cardiac mortality (3.7% vs 20.6%, Plog-rank < 0.001) and rehospitalization events. (7.5% vs 32.2%, Plog-rank = 0.001). Conclusion: Successful revascularization of CTO by PCI may provide clinical benefits in patients with CTO in association with major cardiovascular events.